Information and Parental Consent for French Neonatal Screening: A Qualitative Study on Parental Opinion - Julia Pinel; Amandine Bellanger; Carole Jamet; Caroline Moreau (MDPI AG, 2023)
Neonatal screening has excellent coverage in France. Data from the foreign literature raise questions about the informed consent to this screening. The Neonatal Screening and Informed Consent Dépistage Néonatal Information et Consentement Eclairé (DENICE) study was designed to assess whether information on neonatal screening provided for families in Brittany allows for informed consent. A qualitative methodology was chosen to collect parents' opinions on this topic. Twenty semi-structured interviews were conducted with twenty-seven parents whose children had positive neonatal screening for one of six diseases. The five main themes from the qualitative analysis were knowledge of neonatal screening, information received by parents, parental choice, the experience of the screening process, and parents' perspectives and wishes. Informed consent was weakened by parents' lack of knowledge regarding choice and the absence of a parent after birth. The study found that more information about screening during pregnancy would be preferable. The information should be repeated and accessible and should make it clear that neonatal screening is not mandatory, but informed consent should be obtained from parents who choose to screen their newborns.